2013
DOI: 10.1016/j.pec.2013.06.001
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of patient choices in using emergency health care for long-term conditions: The importance of candidacy and recursivity

Abstract: Strategies that emphasise the need to educate patients about healthcare services use alone are unlikely to change care-seeking behaviour. Practitioners need to modify care experiences that recursively shape patients' judgements of candidacy and their perceptions of accessible expertise in alternative services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
96
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(103 citation statements)
references
References 22 publications
5
96
0
2
Order By: Relevance
“…For instance, other researchers have extended Dixon-Woods' concept and adopted the Candidacy lens when exploring healthcare access across a range of social groups (Hunter et al, 2013;Klassen et al, 2008;Koehn, 2009;Kovandzic et al, 2011;Mackenzie et al, 2013;Purcell et al, 2014) and propose additional dimensions (race, gender, symptom-type), often alongside social disadvantage, that similarly impinge on the Candidacy process.…”
Section: Illness Identity As An Important Component Of Candidacy: Conmentioning
confidence: 99%
“…For instance, other researchers have extended Dixon-Woods' concept and adopted the Candidacy lens when exploring healthcare access across a range of social groups (Hunter et al, 2013;Klassen et al, 2008;Koehn, 2009;Kovandzic et al, 2011;Mackenzie et al, 2013;Purcell et al, 2014) and propose additional dimensions (race, gender, symptom-type), often alongside social disadvantage, that similarly impinge on the Candidacy process.…”
Section: Illness Identity As An Important Component Of Candidacy: Conmentioning
confidence: 99%
“…4 Research focusing on people with long-term conditions suggests that they understand which services are available and choose those that suit them most. 66 They see newer services such as walk-in centres as not offering the technological input of the ED or the established relationship of general practice. The permeability or ease of access of a service affects their choice, with EDs viewed as more permeable than general practice.…”
mentioning
confidence: 99%
“…The permeability or ease of access of a service affects their choice, with EDs viewed as more permeable than general practice. 66 For people with long-term conditions, …”
mentioning
confidence: 99%
“…A newly published study from Great Britain, another country with universal coverage, found many of the same factors driving ED use as did Lawson et al 7 Interviews with 50 individuals, mostly white, of whom 34 were retired, found that prior care experiences and perceived severity of illness were major drivers of ED use. One 62 year-old man with asthma noted that ED staff … know you're having any sort of attack or symptoms related to your asthma, they, they are good.…”
mentioning
confidence: 73%
“…Where in hospital they've got everything there, they've got the ventilators, the drips, they've got everything, they can resuscitate you, if need be (…) I feel safe going in a hospital. 7 It is time to reframe the ED visit, too often viewed as a failure of health care, as the opposite. The modern U.S. ED represents the triumph of a half-century's worth of effort to provide Americans with accessible, affordable, technically and clinically competent, compassionate care at all times.…”
mentioning
confidence: 99%